PHP in a nutshell - Hudson, Paul, 1979- (In a nutshell (O'Reilly & Associates), 2005)
Now installed on more than 20 million Internet domains around the world, PHP is an undisputed leader in web programming languages. Database connectivity, powerful extensions, and rich object-orientation are all reasons for its popularity, but nearly everyone would agree that, above all, PHP is one of the easiest languages to learn and use for developing dynamic web applications. The ease of development and simplicity of PHP, combined with a large community and expansive repository of open source PHP libraries, make it a favorite of web designers and developers worldwide. PHP in a Nutshell is a complete reference to the core of the language as well as the most popular PHP extensions. This book doesn't try to compete with or replace the widely available online documentation. Instead, it is designed to provide depth and breadth that can't be found elsewhere. PHP in a Nutshell provides the maximum information density on PHP, without all the fluff and extras that get in the way. The topic grouping, tips, and examples in this book complement the online guide and make this an essential reference for every PHP programmer. This book focuses on the functions commonly used by a majority of developers, so you can look up the information you need quickly. Topics include: Object-oriented PHP Networking String manipulation Working with files Database interaction XML Multimedia creation Mathematics Whether you're just getting started or have years of experience in PHP development, PHP in a Nutshell is a valuable addition to your desk library.